2016
DOI: 10.5296/elr.v2i2.9842
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Assisted Language Learning: Affordances and Limitations of Duolingo

Abstract: <p class="normal">This study aimed at analyzing how mobile assisted language learning (MALL) may be used to aid second/foreign language (L2) learning. So as to reach this goal, the Duolingo platform, one of the most popular apps among L2 learners, was analyzed in terms of its possibilities and limitations for L2 learning as perceived by its users. With that aim, a study was carried out with 80 participants, 45 of whom were L2 learners who answered an online survey about their preferences for L2 learning,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 13 publications
(16 reference statements)
3
11
0
3
Order By: Relevance
“…Literacy practices to improve competency in English were learned informally outside the school setting, and share the characteristics of vernacular literacies (see Barton & Hamilton, 1998). The use of Duolingo to improve the speaking skill in English is in line with the finding of Finardi, Leao and Amori (2016), who suggested that Duolingo assists language learners with improving their grammar and vocabulary competency. The use of Telegram groups to learn English using a systematic approach through lessons correlated with evidence presented by Abu-Ayfah (2020), who reported that undergraduates employ Telegram for English learning purposes.…”
Section: Improving Competency In Englishsupporting
confidence: 73%
“…Literacy practices to improve competency in English were learned informally outside the school setting, and share the characteristics of vernacular literacies (see Barton & Hamilton, 1998). The use of Duolingo to improve the speaking skill in English is in line with the finding of Finardi, Leao and Amori (2016), who suggested that Duolingo assists language learners with improving their grammar and vocabulary competency. The use of Telegram groups to learn English using a systematic approach through lessons correlated with evidence presented by Abu-Ayfah (2020), who reported that undergraduates employ Telegram for English learning purposes.…”
Section: Improving Competency In Englishsupporting
confidence: 73%
“…With the support from authorities, EFL teachers and learners can engage in collaborative teaching to achieve the success of digital learning of English. Lastly, it is a worth saying E-ISSN: 2528-4479, P-ISSN: 2477-5304 http://jurnal.unissula.ac.id/index.php/edulite DOI: http://dx.doi.org/10.30659/e.5.2.304-321 that society has outreach a point that it is impossible to run away from the advancement of technology, thus it should be seen as a complement rather than an obstacle for second and foreign language learning (Finardi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Jumariati and Febriyanti (2020) agreed that internet connectivity was a crucial aspect that led to successful online learning; once it was in a bad connection, it ruined all the process of learning. Another limitation mentioned by Finardi et al (2016). It was mentioned that the direct interactions among students were decreased in mobile-assisted language learning (MALL).…”
mentioning
confidence: 99%